Reactiveness and inclusiveness as the characteristics of regional labour markets regarding the situation of young people - Bal-Domańska, Beata (Publishing House of Wroclaw University of Economics and Business, 2024)
Having observed the growing number of transnational shocks affecting the national and regional economies, it is worth assessing the condition of regional labour markets, primarily in the con -text of the situation of young people, who for many years have been one of the most vulnerable groups in the labour market. The problem of non-inclusiveness of the labour markets regarding young workers affects both markets presenting high unemployment rates and highly responsive to economic shocks, and also those featuring low youth unemployment rates and stable economic conditions. The article defines models of regional labour markets with regard to the situation of young people in terms of their reactivity of youth labour markets to economic shocks, and their inclusiveness compared to adults.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 1-17